The Implementation of Zona Integritas in Promoting the Accountability at Universitas Negeri Semarang - Widyastuti, Ariyani; Setiawan, Avi Budi (Universitas Negeri Semarang, 2023)
This paper presents the performance accountability at Universitas Negeri Semarang in relation to the importance of zona integritas or integrity zone in increasing the accountability at Universitas Negeri Semarang. This urged an investigation into the extent to which an integrity zone development has been built as a means of increasing accountability at Universitas Negeri Semarang. A quantitative descriptive analysis was carried out in this investigation, starting from data reduction, data presentation, and conclusion drawing. In details, based on respondents’ responses calculated using a Likert scale, it was known that the leader involvement gained the effectiveness of 73.42% in increasing the accountability at Universitas Negeri Semarang. In addition, the leader presence in all stages of planning preparation by 86.25% and 80% of leaders were directly involved in preparing the plans. Meanwhile, the leader monitor for performance achievement on a regular basis gained 85.38%. Of these results, it is suggested that the integrity zone needs to always be improved in terms of maintaining the availability of supporting documents for Universitas Negeri Semarang in the leadership components, involving the parties involved in the leadership components, and completing the management organizational structure.